Model preparation-an effective teaching-learning tool in microbiology - Tripathi, Purti C.; Singh, Himanshu; Suryawanshi, Rahul Kumar (International Journal of Research in Medical Sciences, 2024)
Background: Learning by doing has retention rate of 75%. Working model preparation helps in better understanding of concepts by the students and improves their confidence. They will have a prolonged retention of the topic and its concept thus developing a scientific approach and attitude. The aims were to study the perception of the students for model making, to create students understanding of three-dimensional view of microbiology and to motivate the students to learn microbiology in a better and easy way. Methods: The study was conducted at the department of microbiology, CIMS, Chhindwara. Study participants were second phase MBBS student’s of 2019 batch. 20 Topics were allotted for model preparation. 100 students were divided in 5 different batches. Guidance for model preparation was provided by a mentor of the department. Cost-effective materials such as cardboard, thermocol, paper was used by the students. One week time was given to the students for model preparation. Fifteen days after submission of model a competition was held to motivate students. Results: Most of the students enjoyed the activity, found it useful, interesting, helpful in understanding the concept of the subject, helpful in building logical thinking and gained confidence about the subject. Conclusions: This activity helped the students to showcase their cognitive, psychomotor and communication skills. Constant motivation by teachers to the students shows that slow learners could try to perform well after looking at the other team members.